Pengembangan Media Berbasis Google Sites Pada Materi Dampak Dari Hidup Beriman Dan Berpengharapan Untuk Perserta Didik Kelas VIII SMP Negeri 3 Pakkat Tahun Pelajaran 2023/2024 - Oktavia Andini Simanullang; Lustani Samosir; Baginda Sitompul; Albiner Siagian; Simion Harianja (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The use of learning media is very important to develop efforts to increase students' knowledge, in line with current technological advances, where the learning process cannot be separated from developments in science and technology. This research aims to develop Google sites-based media on the impact of a life of faith and hope for class VIII students at SMP Negeri 3 Pakkat for the 2023/2024 academic year. This type of research is R&D, with a 4-D model modified into 3D, namely define, design and develop, with a quasi-experimental approach, namely in the form of a nonequevalent control group design. Data collection using questionnaires and pretest-posttest. Data analysis uses the Paired sample t-test formula. The results were obtained by comparing the pretest and posttest results between class VIII-A which used Google sites-based media and class VIII-B which used the lecture method. The results of data analysis show that Google Sites-based media learning can increase students' knowledge on the impact of a life of faith and hope. This can be seen from the initial average score for classes using Google Sites-based media of 67.85, increasing to 82.73 with a difference of 14.88. while the control class used the lecture method with an average score of 70.69 to 79.08 with a difference of 8.39. Based on the results, the final average score for the two classes has a difference of 3.65. It can be concluded that learning using Google sites-based media is more effective than the lecture method in increasing students' knowledge on the impact of a life of faith and hope in class VIII SMP Nwgeri 3 Pakkat for the 2023/2024 academic year.